PENGEMBANGAN HYPERMEDIA PADA PEMBELAJARAN EKONOMI KELAS XI IPS DI SMA NEGERI 1 TANJUNG RAJA - Novria Hanifa; Riswan Jaenudin; Dewi Koryati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This research is aimed at producing hypermedia development of valid, practical, and the potential effects of the use of hypermedia produced on student learning outcomes. The model used is a model development Rowntree which consists of three stages, namely planning, development and evaluation phase which has been modified with a formative evaluation Tessmer. To see the validity, the researcher uses a validation performed on the stage of assessment experts (Expert Review) with the average yield - media expert assessment average of 87.5% to the category of Very Good / Very Valid and average - average expert assessment of materials 77.1 % with good category / Invalid. To see the practicalities, carried out at one of the test phase (One To One) through interviews with students and obtained yield was 91.1% and the small group (Small Group) uses a questionnaire with the results of the average - average response of 85.3% of students with Very Good category. As for seeing the potential effects of extensive tests performed on stage (Field Test) using the test results of the initial study (pretest) and the final achievement test (posttest). Field Test in this study conducted in a computer lab SMA Negeri 1 Tanjung King of the number of students as many as 34 people, and the percentage increase in value of 73.6% complete and total average - average value of 91.2% completion has passed classical completeness criteria for 85%, so that the use of hypermedia produced, including effective category. It concluded that hypermedia produced has a valid, practical and effective on subjects economy and can be used as an alternative in the learning process, and is expected to continue to apply a hypermedia learning that has been developed to see the high interest of the students in the learning process through a computer.